Nezavisimye da-formy v voprositel'nyh predloženijah v bolgarskom jazyke - Slavkova, Svetlana (Slavistična revija, 2018)
The article analyzes independent da-forms in Bulgarian interrogative sentences without a li particle. The study focuses on the factors responsible for the realization of the general factual meaning of imperfective verbs in the present and in various past tenses. The distribution of different types of general factual value across different temporal forms is shown with regard to the aspectual concurrence and their Russian counterparts.
Keywords: bolgarščina; da-zgradba; nedovršni vid; skladnja; vprašalni stavki